Elevated Lipid Infiltration Is Associated With Cerebral Aneurysm Rupture - Ou, Chubin; Qian, Yi; Zhang, Xin; Liu, Jiahui; Liu, Wenchao; Su, Hengxian; Zhang, Nan; Zhang, Jianbo; He, Xuying; Duan, Chuan-Zhi (Frontiers in Neurology, 2020)
Background Intracranial aneurysm wall degradation can be associated with lipid infiltration. However, the relationship between lipid infiltration and aneurysm rupture has not been explored quantitatively. To investigate the correlation between lipid infiltration and aneurysm rupture, we utilized patient-specific simulation of LDL transport to analyze lipid infiltration in cerebral aneurysm wall. Methods Sixty two aneurysms were analyzed. Patient blood pressure, plasma LDL concentration and three dimensional angiographic images were obtained to simulate LDL transport in aneurysms. Morphological, hemodynamic and lipid accumulation parameters were compared between ruptures and unruptured groups. Multivariate logistic regression was also performed to determine parameters that are independently associated with rupture. Results Size ratio, wall shear stress, low shear area, relative residence time, area-averaged LDL infiltration rate and maximum LDL infiltration rate were significant parameters in univariate analysis (P<0.05). Multivariate analysis revealed that only average LDL infiltration remained as a significant variable (P<0.05). The prediction model derived showed good performance for rupture prediction (AUC, 0.885; 95% CI, 0.794-0.976). Conclusions Ruptured aneurysms showed significantly higher LDL infiltration compared to unruptured ones. Our results suggested that lipid infiltration may promote aneurysm rupture. Lipid infiltration characteristics should be considered when assessing aneurysm rupture risk.